Tunable exciton–polariton condensation in a two-dimensional Lieb lattice at room temperature - Fabio Scafirimuto (Nature Portfolio, 2021)
Artificial periodic lattices of microcavities filled with optically active materials can serve as a platform to explore a range of physical phenomena. Here, the authors prepare and analyse 2D Lieb lattices made from a tunable cavity array with an organic polymer which operates in the strong exciton–photon coupling regime and exhibits polariton condensation at room temperature.